Efektivitas Asap Cair Sebagai Antioksidan Alami Untuk Menghilangkan Ketengikan Minyak Goreng Curah - Harra Alla, Debora ; Ndjuru Mana, Melvianus Ndena (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Cooking oil is one of the basic needs of the community to fulfill their daily needs. Cooking oilconsumed every day is closely related to health. It is important for us to know the quality ofcooking oil that we use everyday. This study aims to examine the analysis of the quality of bulkcooking oil and eliminate the rancidity of bulk cooking oil by adding liquid smoke as a naturalantioxidant. Liquid smoke from rice husk produced from the pyrolysis process containscellulose, hemicellulose and lignin to produce phenol compounds, acidic compounds and theirderivatives. Can be used as an antioxidant to eliminate rancidity in bulk cooking oil. Theanalysis of the quality of bulk cooking oil is carried out by using observational parameters,namely FFA test, acid number, and peroxide number. The results of the research on bulkcooking oil showed that the value of FFA levels, the value of acid numbers and the value ofperoxide numbers decreased. And meet the requirements of the value of free fatty acids, acidicvalues and peroxide values for cooking oil quality standards.